An analysis of the microencapsulation of ceftiofur in chitosan particles using the spray drying technology. (15th April 2020) - Helbling, Ignacio M.; Busatto, Carlos A.; Karp, Federico; Islan, Germán A.; Estenoz, Diana A.; Luna, Julio A.
Graphical abstract: Highlights: Good encapsulation efficiencies were obtained using the spray drying technology. Microparticles fabrication can be easily scale up for industrial production. Ceftiofur thermal stability enhanced after microencapsulation. Microbicide power was similar between our formulation and the commercial product. Dosage might be extended to 48 h in goats using chitosan microparticles. Abstract: Ceftiofur is a third-generation cephalosporin approved to treat numerous infections in production animals. Its commercial formulations are administered daily due to the mean life time, leading to several inconveniences, like operative challenges and non-uniform plasma levels. The objective of this work was to microencapsulate ceftiofur in chitosan particles using spray drying technology to extend the delivery and consequently reduce the dosage frequency. The effect of formulation factors on particle features was studied using a multilevel factorial design. In addition, ceftiofur thermal stability was assayed by differential scanning calorimetry and microbiological assays. Finally, a pharmacokinetic model was developed to predict theoretical plasma concentration in goats. Results showed that ceftiofur thermal stability increased after microencapsulation, indicating a protective effect of chitosan particles. Besides, MIC, IC50 and inhibition halos against E. coli and S. aureus were similar than those of the commercial product. In addition, suitable plasma levels can be theoretically maintained in goats during 48 h with a single injection. These findings suggest that chitosan microparticles could be a good vehicle for ceftiofur administration.